2007
DOI: 10.2353/ajpath.2007.060834
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts: What Do They Do and How Do They Do It?

Abstract: As Americans live longer, degenerative skeletal diseases, such as osteoporosis, become increasingly prevalent. Regardless of cause, osteoporosis reflects a relative enhancement of osteoclast activity. Thus, this unique bone resorptive cell is a prominent therapeutic target. A number of key observations provide insights into the mechanisms by which precursors commit to the osteoclast phenotype and how the mature cell degrades bone. The osteoclast is a member of the monocyte/macrophage family that differentiates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
487
0
19

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 622 publications
(509 citation statements)
references
References 95 publications
(105 reference statements)
3
487
0
19
Order By: Relevance
“…However, the role of IFN-␥ in pathological bone disease is largely controversial. Previously, it has been reported that IFN-␥ can inhibit the critical osteoclast regulator, receptor activator of NFB ligand (RANKL), by activating ubiquitin-mediated degradation of its signaling pathway adaptor protein TRAF-6 (7,8). Mice deficient for IFN-␥ or its receptor develop enhanced bone loss associated with collagen-induced arthritis (9 -11).…”
Section: Ifn-␥mentioning
confidence: 99%
“…However, the role of IFN-␥ in pathological bone disease is largely controversial. Previously, it has been reported that IFN-␥ can inhibit the critical osteoclast regulator, receptor activator of NFB ligand (RANKL), by activating ubiquitin-mediated degradation of its signaling pathway adaptor protein TRAF-6 (7,8). Mice deficient for IFN-␥ or its receptor develop enhanced bone loss associated with collagen-induced arthritis (9 -11).…”
Section: Ifn-␥mentioning
confidence: 99%
“…First, macrophages are closely related to bone-resorbing osteoclasts and share a dependence on the lineage-specific growth factor CSF-1 (2). Although inflammatory macrophages are well acknowledged for their roles in immunity and chronic inflammation, it is less widely recognized that there are populations of resident tissue macrophages present in most tissues throughout development and adulthood (e.g., alveolar macrophages and Kupffer cells (3)).…”
mentioning
confidence: 99%
“…Osteoclasts are highly specialized cells that have the capacity to resorb bone or, perhaps more accurately, to invade mineralized tissue in a regulated manner (8). They express very high levels of a subpopulation of V-ATPases (a3-and d2-containing V-ATPases) that are targeted to the ruffled plasma membrane, a subdomain of the plasma membrane, when osteoclasts encounter bone (9 -11).…”
mentioning
confidence: 99%